Teachers' Mastery of Pedagogical Competencies in the Learning Process at SMK Negeri 1 Polewali - Saleh, Sirajuddin; Hijrana Wahyudin, Sarifa; Darwis, Muh (Universitas Negeri Makassar, 2023)
A teacher is an educator who is a figure, and role model and has authority and responsibility for the education of students, therefore a teacher must master competencies by continuing to develop the competencies that exist within him. This research aims to determine teachers' mastery of pedagogical competence in the learning process at SMK Negeri 1 Polewali. This research is quantitative research with a descriptive research type. The sample in this study was 59 teachers using simple random sampling techniques. The data collection techniques used are observation, questionnaires, and documentation. Based on the results of this research, show that teachers' mastery of pedagogical competence in the learning process at SMK Negeri 1 Polewali with a percentage level of 91.26%, this shows that teachers' understanding of students, learning materials, developing curriculum, organizing educational learning, utilizing ICT, facilitating the development of students' potential, communicating effectively, empathetically and politely with students, carrying out assessments and evaluations of learning outcomes processes, utilizing assessment and evaluation results for learning purposes, and carrying out reflective actions to improve the quality of learning are in the very good category. The results of this research show that it is important for teachers to master pedagogical competencies to be able to manage learning and encourage students to play an active role in the learning process by creating interesting and enjoyable learning